Crase: ensino contextualizado e produção discente - Letícia Pena Silveira (2020)
This dissertation has a double purpose: to reflect upon the contextualized teaching of crasis in High School and, afterward, to do an experiment of deductive and inductive didactic approaches to verify the efficiency of each of these practices. The motivation for conducting this research arose from my experience with students’ questions regarding the need for learning particular contents that have no relation to their actual use of the Portuguese language. The object of this research is crasis because it was found to be a grammatical topic that students face learning difficulties. As this is a subject in Applied Linguistics, this research is directed mainly to (future) Portuguese language teachers who are looking for ways to redirect the exposure of normative content, especially articulating it with reading and text production. This is important because, according to Antunes (2014), grammar is inherently contextualized, since there is no text without grammar. Moreover, Geraldi (2003 [1991]) had already proposed the practice of Linguistic Analysis as a way of reflecting on the resources that permeate the text. Since this was an Action Research, data were collected in six high school classes (two classes for each of the three grades), in which the researcher is also the students’ teacher. A total of 258 texts were collected. For the first and second grades, an overview of students’ use of crasis was made; in the third grade, in addition to this overview, the experiment was conducted by contrasting the deductive and the inductive-contextualized approach by writing and rewriting texts. It was found, mostly in high school, a number of correct items significantly higher than errors. Therefore, more specific analyzes were performed, resulting in the conclusion that the biggest difficulty lies in placing the stress accent in contexts where it is required. Besides, when checking the classes separately, there was a difference between them, showing different profiles that teachers have to deal with throughout their careers. Finally, the experiment yields that the two forms of teaching tested were successful since there was indeed learning in both. The inductive-contextualized approach, however, stands out in the pleasure acquired by the students during the class, showing that, by bringing them as a protagonist of their teaching-learning process, there is a significant gain concerning the Portuguese language classes reception, which is questioned regarding its need.